2017
DOI: 10.1101/230631
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-Invasive Brain Stimulation to Investigate Language Production in Healthy Speakers: A Meta-Analysis

Abstract: Non-invasive brain stimulation (NIBS) has become a common method to study the interrelations between the brain and language functioning. This meta-analysis examined the efficacy of transcranial magnetic stimulation (TMS) and direct current stimulation (tDCS) in the study of language production in healthy volunteers. Forty-five effect sizes from 30 studies which investigated the effects of NIBS on picture naming or verbal fluency in healthy participants were meta-analysed. Further sub-analyses investigated pote… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 90 publications
(145 reference statements)
2
10
0
Order By: Relevance
“…It should be noted, however, that these analyses are based on one significant (i.e., from the lexical decision task) and one non-significant main effect of tDCS (i.e., from the sentence comprehension task). Interestingly though, the same pattern was found by Klaus and Schutter (2018), where the effect of tDCS on the left dorsolateral prefrontal cortex on three different tasks (picture naming, sentence comprehension, Flanker task) was tested. Both findings suggest that there are differences in the magnitude of the tDCS effect between individuals, adding to the existing literature on between-participant variability in response to tDCS (Cheeran et al, 2017;López-Alonso et al, 2015;Wiethoff et al, 2014).…”
Section: Figure 4 Results From Exploratory Analyses Including Cognitive Load (High Vs Low) In the Rt Analysis Of The Sentence Comprehensisupporting
confidence: 66%
See 2 more Smart Citations
“…It should be noted, however, that these analyses are based on one significant (i.e., from the lexical decision task) and one non-significant main effect of tDCS (i.e., from the sentence comprehension task). Interestingly though, the same pattern was found by Klaus and Schutter (2018), where the effect of tDCS on the left dorsolateral prefrontal cortex on three different tasks (picture naming, sentence comprehension, Flanker task) was tested. Both findings suggest that there are differences in the magnitude of the tDCS effect between individuals, adding to the existing literature on between-participant variability in response to tDCS (Cheeran et al, 2017;López-Alonso et al, 2015;Wiethoff et al, 2014).…”
Section: Figure 4 Results From Exploratory Analyses Including Cognitive Load (High Vs Low) In the Rt Analysis Of The Sentence Comprehensisupporting
confidence: 66%
“…In the motor cortex, anodal tDCS is thought to increase spontaneous neural firing, leading to performance improvement, whereas cathodal tDCS decreases cortical excitability, causing a performance decrement (Fernandes Medeiros et al, 2012;Nitsche et al, 2008). However, work focusing on brain areas outside of the motor cortex has suggested that this dichotomy may be less straight-forward for non-motor cortical regions (Brückner & Kammer, 2017;Klaus & Hartwigsen, 2020;Klaus & Schutter, 2018) including the cerebellum (Oldrati & Schutter, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample consisted of 40 patients, 13 males (32.5%) and 27 females (67.5%), with mean age of 73.17 ± 5.61 years (age range 62-80), mean education of 12.7 ± 3.58 years (education range [8][9][10][11][12][13][14][15][16][17][18].…”
Section: Participantsmentioning
confidence: 99%
“…NIBS is being increasingly used to study the connection between language processes and the underlying brain networks [8][9][10][11][12][13][14][15]. Just as an example, recent studies have reported that in healthy subjects inhibitory repetitive TMS (rTMS) over the right lateral frontal cortex significantly improves phonemic fluency performance [16], while excitatory tDCS over the left inferior frontal gyrus improves performance in naming, phonemic, and semantic fluency tasks [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%